Marketing Scenario of Fruits and Vegetables in Kerala - G.S. Sreekala,; P.G. Sadan Kumar,; S.Nirmala Devi, (Journal of Agricultural Extension Management, 2025)
The vegetable and fruit marketing system in Kerala involves a long chain of intermediaries taking exorbitant margins resulting in low farmer's share in consumer's price. The involvement of intermediaries results in multiple handling, loss of quality, malpractices in weighment, handling, payments etc. Vegetable and fruit cultivation in Kerala is predominantly undertaken by small, marginal farmers and landless agricultural workers who lease the land. In order to sustain the interest of vegetable and fruit growers and motivate them for enhancing production, it is necessary to ensure that they get a reasonable price. A marketing channel which ensures a good and reasonable price to the producers as well as consumers with least number of intermediaries has to be identified. Due to interventions by public sector organizations, vegetable and fruit marketing in Kerala has improved the farmers ' share of consumers price. This paper reviews the role of public sector organisations, their interventions in vegetable and fruit marketing in Kerala, strengths and weaknesses.